Study on Bumiko promotional activities: Bumiko Sdn Bhd Jalan Simpang Tiga, Kuching / Arenawati Sehat Omar - Omar, Arenawati Sehat (2000)
The objectives of the study are to analyze the implementation of promotion activities and also to seek out the appropriate suggestions and recommendations in order to improve the existing promotion activities of the company.Promotion is one of the four major elements of the company's marketing mix or 4P's. The result shows that this company has carried out sufficient promotion activities in their business such as advertising through radio and newspaper to inform the public or their target customers about their business. In facing the future challenges, the company also concerns about their quality of service that is believed will help them to survive in their business. The survival of the business almost lies in the hand of the customers. Customers play a very important role for the business sustainability in today's competitive business world Majority of their customers agreed that the company always tries to keep long-term relationship and satisfied their customer. The company has also succeeded in promoting their loan facilities as their main attraction to welcome their customers to their company. This has been proved that majority of the respondents or customers choose this as their main reason to make their buying decision at the outlet.